Influence of Carbon Concentrations in Reducing Co and Cr Ions Release in Cobalt Based Implant: A Preliminary Report - Rosdi, Daud; Mas Ayu, Hassan; S., Izman; Mohammed Rafiq, Abdul Kadir; A., Shah; Mohd Faiz, Mohd Yusoff; M. W., Shamsiah; T. M., Yong; T., Kamarul (Elsevier, 2014)
The releases of harmful ions from cobalt based alloy to host tissues have raised significant health concerns. Carbon contents in this alloy may influence ions release but has yet investigated. It is hypothesized that carbon contents in this alloy will help the formation of oxide layer during thermal oxidation process and hence reducing the release of Co/Cr ions after implantation. In this study, Co-Cr-Mo alloy with carbon concentrations of 0.03% and 0.24% were oxidized at 1050°C for 3 hours under atmospheric condition. The oxidized substrates were characterized under FESEM and subjected to circulating immersion test in simulated body fluid (SBF) for 21 days. Metal ions release was measured using inductively coupled plasma-mass spectrometry (ICP-MS) at day 0, 7, 14 and 21. Oxidized high carbon samples show denser and a more uniform oxide layer than samples with low carbon contents. It is found that compact oxide structure promotes less metal ions release during immersion.